Wykorzystanie funduszy unijnych na rzecz wspierania przedsiębiorczości na obszarach wiejskich (na przykładzie woj. lubuskiego) - Wojewoda, Izabela (The Use of EU Funds for Supporting the Entrepreneurship in Rural Areas (on the Example of Lubuskie Voivodship), 2005)
The transformations in Polish agribusiness after the integration is the desirable direction of changes in the structure of employment in rural areas and the progress of beyond the agriculture's activity. The changes are supported by means from national programmes and local authorities programmes, but also from the EU. However, the EU emphasizes the meaning of multifunctional development of rural areas, and directs the financial means precisely to "around" agricultural development of Polish countryside. The obstacle in their full usage is modest knowledge of businessmen on support forms, quite a big bureaucracy, formalisation of applications and incompatibility of Polish law to using the EU funds and lack of comprehensive information about them. The article presents the interest of the EU support for entrepreneurship and multifunctional development of rural areas on the example of Lubuskie voivodship.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 411-415